Instrumented impact test of duplex stainless steel miniature specimen. Issue 9 (14th September 2013) - Wunder, J.; Karl, A.; Dwars, A.; Böhm, A.
Abstract The paper describes a new approach to characterize metallic materials by a novel instrumented notch impact test for samples with small specimen size. A piezo‐electric sensor mounted on the pendulum hammer provides force information during the fracture process. By numerical integration of the signal the absorbed impact energy can be calculated very exactly. Further information about the fracture behavior can be extracted from the resulting force‐displacement‐diagram. Several duplex stainless steels in different heat treatment conditions were tested and compared to standard Charpy impact testing specimen. It is concluded that different grades of embrittlement of duplex materials can be detected with high accuracy. Due to a data acquisition rate of 250 kilo‐samples/second and limited stiffness of the pendulum hammer impact energies of less than 7% of maximum energy materials with high brittleness can only be characterized qualitatively.